Machine-tool industry retrospective analysis in member countries of the Commonwealth of Independent States - M. M. Shailieva; K. N. Sergeeva (Управление)
The article examines the dynamics of machine tool production in the countries of the Union of Soviet Socialist Republics (USSR) and post-Soviet states from the standpoint of statistical science. In the course of the work a data was obtained, the tabular and graphical presentation of which made it possible to identify certain periods of time in the machine tool industry of the USSR and the Commonwealth of Independent States (including the Baltic states), characterized by different dynamics and production structure in individual states. The initial stage of development fell on the territory of modern Russia, but during the years of the existence of the USSR, a number of machine-tool industries were opened in the Union Republics. This gave impetus to industrial development on the periphery of the Soviet state, and by the time the domestic machine tool industry flourished in the late 1970s, the Russian Soviet Federative Socialist Republic accounted for less than half of the all-Union output. However, after 1978 there was a significant decline in the dynamics of production in the industry. And after the collapse of the country there is almost complete destruction of the machine-tool industry on the territory of the countries of the former USSR. The results obtained in the course of the study can be useful in scientific and practical activities in assessing the current situation, as well as prospects for the production and consumption of machine tools in the countries of the Commonwealth of Independent States, including Ukraine and the Baltic states.